The Influence of Emotional Intelligence on The Learning Outcomes of Pastry and Bakery Culinary Students of SMK Negeri 6 Padang - Putri, Febrila Angria; Yulastri, Asmar; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the lack of learners' ability to control emotions so that it is difficult to think and focus on learning. This problem is an individual factor that causes students to be unable to provide encouragement to themselves to focus on learning, so that many students have scores below the minimum criteria completeness (KKM) in Pastry and Bakery subjects. The purpose of this study was to analyze the effect of students' emotional intelligence on learning outcomes in pastry and bakery subjects at SMK Negeri 6 Padang. This research method is quantitative with the type of expost facto research (casual research). The population in this study were XI and XII culinary majors at SMK Negeri 6 Padang as many as 197 students. The research sample amounted to 66 students with the sampling technique is random sampling. The primary data collection technique in this study was a questionnaire and the secondary was documentation. The results of descriptive analysis of this study are emotional intelligence is stated to be strong so that it can improve student learning outcomes. Test the success of the correlation coefficient with a coefficient interval of 1.000 with the level of relationship between the two variables is strong. The results of the T test with T table 2.954 are greater than Thitung 1.669 so that there is an influence of emotional intelligence on the learning outcomes of pastry and bakery culinary students at SMK Negeri 6 Padang.